Teologi Konvergensi dan Kerukunan Antar Umat Beragama - Zuhriyah, Lailatuz (Religió: Jurnal Studi Agama-agama, 2014)
Religion does not occur in human life as a single reality, which cannot be separated from historical and cultural realm. It consists achievement of rational and spiritual domain, supporting historical needs of mankind life. Religion presents itself as an inseparable part of human history at various level of civilizations. When debate of truth claims and salvation becomes a major theme, the theology of convergence is needed to create inter-religious harmony. The main purpose of theological convergence is to unite essential elements of religion. Religion and its adherents can be unified in one concept of universal theology. If convergence theology can be fully understood, it surely will build inter-religious harmony. Besides bring opportunities to create inter-religious harmony, theological convergence also faced a number of challenges that will be an obstacle to the realization of the ideals of society for religious harmony. Therefore, before apply the convergence of theological discourse to the society, we need to identify the challenges that will be faced in order to minimize the negative possibilities that may hamper the main objective theological convergence. Therefore, this paper will also be focused on the discussion about the challenges of theological convergence